Die Ultraschallsprechstunde: Eine Ethnografie pränataldiagnostischer Situationen - Heimerl, Birgit (transcript, 2014)
How do the unborn figure into the picture by ultrasound? How do the participants in a clinical session organize the social relationship in which they are involved for diagnostic purposes? Birgit Heimerl's ethnography on the practice of prenatal ultrasonography and accompanying consultation focuses on the clinical situation and situated practices, which are reconstructed on the basis of participant observation. The analysis draws on the micro-sociology of Erving Goffman and praxeological notions of sociality. It shows, among other things, how the unborn are sonographically expressed and »embodied« as epistemic objects of knowledge of prenatal diagnosis and how this is communicatively and interactively framed.